2015
DOI: 10.1021/jacs.5b01566
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of an Amphiphilic Assembly by Calixarene-Induced Aggregation

Abstract: Photosensitizers generally show great tendency for self-aggregation in aqueous media, leading to quenched fluorescence and lower photosensitizing ability. Herein, we report that amphiphilic anthracene is highly photoreactive after aggregation induced by p-sulfonatocalix[4]arene in water. The formation of a host-guest supramolecular assembly and the photolysis of the anthryl core are identified by UV-vis and NMR spectroscopy, dynamic light scattering, and transmission electron microscopy. Additionally, the asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 124 publications
(59 citation statements)
references
References 66 publications
1
54
1
Order By: Relevance
“…Alternatively, 9-alkoxyanthracenes such as 17 can be synthesized via base mediated proton abstraction at the methylene bridge, followed by alkylation of the formed anion with alkyl halides. 20 By adding undecenoyl chloride instead of alkyl halides to anthrone 16, after addition of a (strong) base and allowing enol rearrangement, ester 19 was synthesized in good yield (84%).…”
Section: Synthesis Of Anthracene Derivativesmentioning
confidence: 99%
“…Alternatively, 9-alkoxyanthracenes such as 17 can be synthesized via base mediated proton abstraction at the methylene bridge, followed by alkylation of the formed anion with alkyl halides. 20 By adding undecenoyl chloride instead of alkyl halides to anthrone 16, after addition of a (strong) base and allowing enol rearrangement, ester 19 was synthesized in good yield (84%).…”
Section: Synthesis Of Anthracene Derivativesmentioning
confidence: 99%
“…Recently, we have developed a novel strategy for the construction of supramolecular assemblies by means of host induced aggregating ( HIA : a small amount of macrocyclic host could promote the aggregation of guest molecules by lowering the critical aggregating concentration ( CAC ) and even regulating the morphology of the aggregates)5051525354555657. So after successful establishing the recognition motif between 2C-WP5A and G in aqueous solution, we were trying to explore the constructing supramolecular aggregates based on 2C-WP5A and trans- G .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we constructed a photodegradable supramolecular assembly utilizing p‐sulfonatocalix[4]arenes (SC4 A) and amphiphilic 9‐alkoxy‐substituted anthracene, and the results showed that the amphiphilic anthracene was highly photoreactive after aggregation induced by SC4 A in water . Herein, a photodegradable supramolecular assembly was designed with sulfato‐β‐cyclodextrin (SCD) as the host and 2‐pyridinium alkoxy‐substituted anthracene (Anpy) as the guest by molecular induced aggregation (Scheme ).…”
Section: Methodsmentioning
confidence: 99%